The Influence of Differentiated Learning Models on the Learning Outcomes of Fifth Grade Students in Mathematics - Rahman, Makbul; Akrom, Muhamad; Taufik, M. (Polyhedron International Journal in Mathematics Education, 2024)
This study aimed to determine the effect of differentiated learning models on the learning outcomes of fifth-grade students in mathematics at elementary school in the 2023/2024 academic year. The study was conducted on fifth-grade students with a population of 21 students as one sample. The sampling technique used in this study was saturated sampling, where all populations were used as one sample. This study was an experimental study with a pre-experimental design, specifically a one-group pretest-posttest design. The pretest was used to measure students' initial abilities, while the posttest was conducted to measure the learning outcomes of fifth-grade students after carrying out treatment or action. Hypothesis testing in this study used the Paired Sample T-Test, which was preceded by a validity test, reliability test, and normality test. The results of this study were seen from the hypothesis test carried out using the Sample Paired T-Test technique, which obtained a significant value of 0,000. This means 0,000 < 0,05, so H1 was accepted. It can be concluded that there was an influence of the differentiated learning model on the learning outcomes of fifth-grade students in mathematics.